ABUSE OF AUTHORITY BY VILLAGE HEADS IN THE COMPLETE SYSTEMATIC LAND REGISTRATION PROGRAM (PTSL) (Case Study of Cikupa Village for Fiscal Year 2021) - Zamzami Sulthony, Razy; Albab, Ulil; Amiludin, Amiludin (Justisi: Jurnal Ilmu Hukum, 2024)
Abuse of authority by individual village heads in the Complete Systematic Land Registration Program (PTSL) is an important and interesting issue to research. This research aims to identify and analyze cases of abuse of authority that occurred in Cikupa Village in the 2021 fiscal year. The research method used is a case study with an empirical normative approach. Data was obtained through observation and document study. The research results show indications of abuse of authority by individual village heads in implementing PTSL, including misuse of funds, manipulation of data, and violations of procedures. The implication of these findings is the need for strict preventive and law enforcement measures to prevent abuse of authority in the future and ensure the continued success of PTSL implementation. This research makes an important contribution in understanding the dynamics of land program implementation at the local level and highlights the importance of transparent and accountable governance in the implementation of village government. Keywords: Cikupa Village, Complete Systematic Land Registration (PTSL).